2018
DOI: 10.1080/09638288.2018.1496152
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of the cognitive orientation to daily occupational performance approach in young adults with spina bifida or cerebral palsy: a feasibility study

Abstract: Purpose: People with cerebral palsy (CP) or spina bifida (SB) often struggle to perform everyday-life activities. Both groups frequently also have difficulties in creating and using strategies effectively when performing tasks. The cognitive orientation to daily occupational performance (CO-OP) Approach combines the learning of cognitive strategies with task-specific approaches through a client-centred procedure. The aim of this study was to investigate whether the COOP Approach is feasible for and potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 54 publications
1
57
0
Order By: Relevance
“…Another innovation has been to test the feasibility, acceptability, and preliminary efficacy of a cognitive-based intervention known as cognitive orientation to occupational performance (CO-OP) [270]. CO-OP was originally designed for the developmental coordination disorder population where dyspraxia is the most important clinical sign [270], but now has promising evidence of efficacy for cerebral palsy, especially the dystonic type where treatment options are lacking [73][74][75][76]. In CO-OP, children set their own goals and are guided to discover and individualize strategies for successfully carrying out their goals, via a global problem-solving strategy "goal-plando-check" [270].…”
Section: Cognitive Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another innovation has been to test the feasibility, acceptability, and preliminary efficacy of a cognitive-based intervention known as cognitive orientation to occupational performance (CO-OP) [270]. CO-OP was originally designed for the developmental coordination disorder population where dyspraxia is the most important clinical sign [270], but now has promising evidence of efficacy for cerebral palsy, especially the dystonic type where treatment options are lacking [73][74][75][76]. In CO-OP, children set their own goals and are guided to discover and individualize strategies for successfully carrying out their goals, via a global problem-solving strategy "goal-plando-check" [270].…”
Section: Cognitive Interventionsmentioning
confidence: 99%
“…Once the child has self-identified a successful strategy, they practice the real-life task at high intensity, similar to other motor learning approaches [98]. Four studies have now been conducted in the cerebral palsy population suggesting CO-OP improves function at a low dose and low cost with large effect sizes (yellow light, weak positive) [73][74][75][76]. The conduct of a definitive trial is warranted.…”
Section: Cognitive Interventionsmentioning
confidence: 99%
“…The participants in this study are the same individuals who participated in the feasibility study [23]. They were recruited through habilitation services in two different parts of Sweden.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…To the best of our knowledge, this approach has not been used in those groups. Hence it was decided to conduct a pilot study [23]. The result from this study showed that COOP is a promising approach for enabling young people with cerebral palsy or spina bifida to achieve their personal goals and to enhance their occupational performance and executive functioning through strategy use [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation